Band structure of [100] surface of Cd₁₋x Mn x Te diluted magnetic semiconductor - Melnichuk, S.V.; Mikhailevsky, Y.M.; Rarenko, I.M.; Yurijchuk, I.M. (Condensed Matter Physics, 2000)
Electronic band structure of the diluted magnetic semiconductor
Cd₁₋x Mn x Te [100] ideal surface is calculated by the semiempirical tight-
binding method in the framework of sps*-model. Surface bands, emerging
above the bulk band structure, as well as their type, energy position and localization near the parting border with vacuum are investigated. It is shown
that Mn 3d-states as well as sp-states play appreciable role in the formation
of surface bands. The peculiarities of surface band structure are analyzed
in the dependence of solid solution composition. Розраховано електронну зонну структуру iдеальної поверхнi [100]
напiвмагнiтного напiвпровiдника Cd₁₋x Mn x Te в sps*-моделi сильного зв’язку, що включає катiоннi d -орбiталi. Вивчено зони поверхневих станiв, якi виникають на фонi спектра об’ємного кристалу, їх
тип, енергетичне положення та просторову локалiзацiю бiля границь
роздiлу з вакуумом. Показано, що поряд з sp -станами помiтну роль
у формуваннi поверхневих станiв вiдiграють 3d -стани Mn. Аналiзуються особливостi спектра поверхнi залежно вiд складу твердого
розчину.